PROYEKSI PENDUDUK, PERAN KB NASIONAL, DAN IMPLIKASINYA TERHADAP PEMBANGUNAN - Murjana Yasa, I.G.W (PIRAMIDA; Vol. 2, No. 1 Juli 2006, 2012)
Until near in the year of 2015, population growth is estimated around 1,26 percent per year, after that in accordance with the changing of child possession pattern and population aging structure, fertility rate and mortality rate are estimated to be increase. Life expectancy on average in Bali is estimated to increase from 70,6 year in 2000 become 74,6 year in 2025. There is an interesting matter that need to be concerned related to trend of bali population structure, that is since 2000 dependency ratio of Bali population is under 50 which is estimated to be take place until the end of projection period. This is a ?golden age? where the burden of productive population is not too heavy. This condition is also become a demographic gift because there is an economic advantage which is caused by decresing of dependency ratio as a concequence of long run fertility decline. Relative success in pressing population growth rate is irrespective of the role of family planning program which is continously adjusting its programs with population development. In the future, in relation with shifting in population parameter, there are some matters that must be concerned especially related to the implication on development : 1) keeping the momentum of succes pressing fertility and mortality rate and population mobility control, 2) more creative in implementing population control, 3) exploiting demography gift by implementing several programs of population quality improvement through productivity improvement
Keywords: aging, demographic gift, productive